ИСТОРИЧЕСКИЙ РОМАН И СЮЖЕТ (Лучшие интеллектуальные исследования, 2025)
Аннотация. Статья посвящена одной из актуальных проблем каракалпакского литературоведения. В статье рассмотрены каракалпакский исторический роман и стилевые особенности писателей К.Мамбетова, К.Матмуратова, А.Султанова и К.Каримова. Исследования каракалпакских ученых К.Аймбетова и Т.Алланазарова творчески используется этими писателями. Автор отмечает художественные искания писателей К.Мамбетова, К.Каримова и А.Султанова и особенности жанра исторического романа.Abstract. The article is devoted to one of the urgent problems of Karakalpak literary criticism. The article examines the Karakalpak historical novel and stylistic features of the writers K.Mambetov, K.Matmuratov, A.Sultanov and K.Karimov. The research of Karakalpak scholars K.Aimbetov and T.Allanazarov is creatively used by these writers. The author notes the artistic searches of the writers K.Mambetov, K.Karimov and A.Sultanov and the features of the historical novel genre.